Using the Rational Method to Design a Cutting Tempe - Jakaria, Ribangun Bamban (2477 - 6165, 2023)
Tempe chips are the production processed products made from tempe; the market for this sale is all circles. Various ages and groups can consume it because it is reasonably affordable. Tempe chips are light snacks made from processed tempe that has gone tthrough several production processes. The production process carried out by business actors depends on their respective capabilities, up to the standardization of the cuts reflected in who processes them and from which Small and Medium Enterprises (SMEs). It is from the obstacles faced by SME business players. So that the redesign that will be carried out in this study is to add attributes not found in previous studies, namely tools that can produce tempe slices with low water content so that it will shorten the production process again and increase the efficiency of production time, the research method used is the rational method. It is expected to shorten the estimated costs and improve production results. This research can help SME business owners in their production process, significantly cutting